Implementasi Atau Coding Perangkat Lunak Scoring Cabang Olah Raga Gateball Di Lapangan Siwa Candi Prambanan DIY - Budi Suyanto; Herry Sofyan; Yuli Fauziah (Jurnal Kabar Masyarakat, 2023)
Inspection and implementation of ICT in competition management at Next Gen’s Party Koi Show #2. Training with two-way interaction methods, presentations and exercises on how to use the activity registration application and back office application to manage activity participants and provide support on activity days. Next Gen’s Party Koi Show #2 Online Registration Application Install Next Gen’s Party Koi Show #2 Back Office Online Application Install Next Gen’s Party Koi Show #2 Participant Registration Support Activities Next Gen Support Committee Party Koi Show #2 activities in Participant management.)